Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1093/mnras/stt858
|View full text |Cite
|
Sign up to set email alerts
|

Quadrupole moments of rotating neutron stars and strange stars

Abstract: We present results for models of neutron stars and strange stars constructed using the Hartle-Thorne slow-rotation method with a wide range of equations of state, focusing on the values obtained for the angular momentum J and the quadrupole moment Q, when the gravitational mass M and the rotational frequency Ω are specified. Building on previous work, which showed surprising uniformity in the behaviour of the moment of inertia for neutron-star models constructed with widely-different equations of state, we fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 55 publications
8
109
0
Order By: Relevance
“…Notice the linear behavior of the Kerr factor and its subsequent approach to the value 1 in the limit R/R S → 1.125. These results agrees with those in [65] and [101]. In their original paper Chandrasekhar & Miller [21] found that the quadrupole moment, in units of J 2 /R s , is Q = 2.002 at the Buchdahl radius R = (9/8)R S .…”
Section: Surface and Integral Properties Of Schwarzschild Stars For Rsupporting
confidence: 87%
“…Notice the linear behavior of the Kerr factor and its subsequent approach to the value 1 in the limit R/R S → 1.125. These results agrees with those in [65] and [101]. In their original paper Chandrasekhar & Miller [21] found that the quadrupole moment, in units of J 2 /R s , is Q = 2.002 at the Buchdahl radius R = (9/8)R S .…”
Section: Surface and Integral Properties Of Schwarzschild Stars For Rsupporting
confidence: 87%
“…Also, the power spectral fits of Ingram & Done (2012a) predict that the hot inner flow (corona) has a small scale height in the relevant spectral state. approximated fairly well by the Kerr metric (Török et al 2010(Török et al , 2012Urbanec et al 2013). Therefore, such a finding sets conditions and constraints for the applicability of our results for the case of LMXBs with neutron star.…”
Section: Introductionsupporting
confidence: 73%
“…We note that Kerr geometry represents an applicable approximation of NS spacetimes when the compact object mass is high Urbanec et al 2013). The above formulae valid for Kerr spacetimes well describe (epicyclic) slightly perturbed circular geodesic motion.…”
Section: Twin Peak Qpo Models Approximated In Kerr Spacetimesmentioning
confidence: 61%
“…Thus, when a given EoS is assumed, only corresponding 2D surface is relevant for fitting of datapoints by a given QPO model. Following Urbanec et al (2013), we illustrate such a surface in the right panel of Figure 3 for the SLy4 EoS. The colorcoding of the plot is the same as the one in the left panel of the same Figure. The final M − j map for the RP model and Sly4 EoS, i.e., the values of M and j implied by the common consideration of both panels of Figure 3, is shown in the left panel of Figure 4.…”
Section: Consideration Of Ns Models Given Bymentioning
confidence: 99%